Comparison of Clinical Outcomes and Complications between Closed Suction Drainage and No Drainage after Total Knee Arthroplasty - Wichan, Woraphot (Journal of The Department of Medical Services, 2021)
Background : Closed suction drainage has been widely used when performing total knee arthroplasty, however, benefits and disadvantages of this procedure remain no consensus in various studies.Objective : This study aimed to compare the effect of drain use with no drain after total knee arthroplasty in Thabo Crown Prince Hospital. All operations were performed by a single surgeon.Method : 284 patients who underwent total knee arthroplasty between 1 January 2013 -30 June 2019 were recruited. Patients were divided into two groups according to whether they received a drain postoperatively following total knee arthroplasty. Both groups were compared for rate of blood transfusion, length of hospital stay, time from surgery to initial physical therapy, ecchymosis, hematoma formation and rate of infection.Results : The transfusion rate in the drain group were not significantly different compared to the no-drain group (p=0.158). No significant differences in the time from surgery to initial physical therapy between two groups (p=0.287). The mean of length of hospital stay was 7.68 days for drain group and 7.09 days for non-drain group but there was no difference between two groups (p=0.060). Superficial wound infection occurred 3 cases in both groups but there was no difference between two groups (p=0.761). Ecchymosis were more in non-drain group but there was no difference between two groups (p=0.128). No hematoma formation and no deep wound infection were encountered in both groups.Conclusion : No significant different was observed in the two groups with respect to blood transfusion, infection rate, ecchymosis, time from surgery to initial physical therapy and duration of hospital stay.